Application of dynamic navigation technology in the extraction of complex mandibular third molars with surrounding cystic lesions - HOU Xiaoru; HU Xiaoyi; LI Yanqiu; LI Lifeng; TU Junbo; XING Xiaotao (Kouqiang hemian waike zazhi)
[Objective:] To explore the feasibility of extraction of mandibular third molars with cystic lesions under the guidance of a dynamic navigation system (DNS). [Methods:] Retrospectively analyzed hospitalized patients with lower impacted mandibular third molars in Hospital of Stomatology, Xi'an Jiaotong University from December 15, 2022 to April 15, 2023. According to the inclusion criteria, seven patients with the complex mandibular third molars accompanied cystic lesions, which was tightly adjacent to the inferior alveolar canal were included. All the CT imaging data were imported into the DNS and completed the navigation design. Then the molar were extracted, and cyst was removed under the guidance of navigation. The surgical condition and postoperative recovery state were further analyzed, focusing on the symptoms of postoperative inferior alveolar nerve injury (IANI). [Results:] All patients' wounds healed uneventfully with the application of DNS and the patients had no symptoms of IANI. [Conclusion:] The DNS technology determines the operation position in real time, which reduces the damage of the inferior alveolar neural canal and reduces the risk of inferior alveolar nerve damage.